Considering multiple levels of influence on adjustment in school: Ethnic–racial public regard, peer socialization, and social‐emotional learning practices. Issue 3 (12th January 2021) - Hoffman, Adam J.; Pullés, Stephanie A.; Medina, Michael A.; Pinetta, Bernardette J.; Rivas‐Drake, Deborah; Schaefer, David R.; Jagers, Robert J.
Abstract: Adolescence represents a developmental period of marked increase in the development of ethnic–racial identity (ERI) and the importance and influence of friends. Moreover, scores of studies have revealed that ERI and friendships are influential factors in many different academic and psychosocial outcomes for adolescents. However, the development of these relations between ERI, friendships, and academic and psychosocial adjustment do not occur in a vacuum. One context that likely shapes these relations is the classroom. In the current study, we investigated how ERI and peer socialization were related to academic and social efficacy over time, and how perceptions of social‐emotional learning (SEL) practices in the classroom moderated these relations among 586 American middle school youth. Our analysis tested these hypothesized effects, controlling for potentially confounding the effects of friend selection. Results indicated that more positive ethnic–racial public regard predicted gains in students' perceived social efficacy with teachers but not their perceived social efficacy with peers or academic efficacy. In the assessment of peer socialization effects, youth became increasingly similar to their peers in regard to academic efficacy, social efficacy with peers, and social efficacy with teachers over time. Moderation analyses indicated that perceptions of greater exposure to SEL practices reduced students' susceptibility to their friends' influence in social efficacy with teachers. Together, these results highlight the unique and combined impact of ERI, peer influence, and SEL in the development of adolescents' social efficacy.